Chromosomal mosaicism in human blastocysts: the ultimate diagnostic dilemma. (6th March 2020) - Popovic, Mina; Dhaenens, Lien; Boel, Annekatrien; Menten, Björn; Heindryckx, Björn
Abstract: BACKGROUND: Trophectoderm (TE) biopsy and next generation sequencing (NGS) are currently the preferred techniques for preimplantation genetic testing for aneuploidies (PGT-A). Although this approach delivered important improvements over previous testing strategies, increased sensitivity has also prompted a rise in diagnoses of uncertain clinical significance. This includes reports of chromosomal mosaicism, suggesting the presence of karyotypically distinct cells within a single TE biopsy. Given that PGT-A relies on the chromosomal constitution of the biopsied cells being representative of the entire embryo, the prevalence and clinical implications of blastocyst mosaicism continue to generate considerable controversy. OBJECTIVE AND RATIONALE: The objective of this review was to evaluate existing scientific evidence regarding the prevalence and impact of chromosomal mosaicism in human blastocysts. We discuss insights from a biological, technical and clinical perspective to examine the implications of this diagnostic dilemma for PGT-A. SEARCH METHODS: The PubMed and Google Scholar databases were used to search peer-reviewed publications using the following terms: 'chromosomal mosaicism', 'human', 'embryo', 'blastocyst', 'implantation', 'next generation sequencing' and 'clinical management' in combination with other keywords related to the subject area. Relevant articles in the English language, published until October 2019 were critically discussed. OUTCOMES: Chromosomal mosaicism predominately results from errors in mitosis following fertilization. Although it appears to be less pervasive at later developmental stages, establishing the true prevalence of mosaicism in human blastocysts remains exceedingly challenging. In a clinical context, blastocyst mosaicism can only be reported based on a single TE biopsy and has been ascribed to 2–13% of embryos tested using NGS. Conversely, data from NGS studies disaggregating whole embryos suggests that mosaicism may be present in up to 50% of blastocysts. However, differences in testing and reporting strategies, analysis platforms and the number of cells sampled inherently overshadow current data, while added uncertainties emanate from technical artefacts. Moreover, laboratory factors and aspects of in vitro culture generate further variability. Outcome data following the transfer of blastocysts diagnosed as mosaic remain limited. Current studies suggest that the transfer of putative mosaic embryos may lead to healthy live births, but also results in significantly reduced ongoing pregnancy rates compared to the transfer of euploid blastocysts. Observations that a subset of mosaic blastocysts has the capacity to develop normally have sparked discussions regarding the ability of embryos to self-correct. However, there is currently no direct evidence to support this assumption. Nevertheless, the exclusion of mosaic blastocysts results in fewer embryos available for transfer, which may inevitably compromise treatment outcomes. WIDER IMPLICATIONS: Chromosomal mosaicism in human blastocysts remains a perpetual diagnostic and clinical dilemma in the context of PGT-A. This review offers an important scientific resource, informing about the challenges, risks and value of diagnosing mosaicism. Elucidating these uncertainties will ultimately pave the way towards improved clinical and patient management.